VD_FINDINFO AI 82/23 - 179/2024 vom 9. April 2024 - VD Tribunal cantonal (2024)
INDEMNITÉ JOURNALIÈRE, AIASSURANCE | 16 al. 1 LAI, 22 al. 1bis LAI, 8 al. 1 LAI, 8 al. 3 let. b LAI, 22 al. 1 RAI, 22 al. 2 RAI, 5 RAI